2021
DOI: 10.7150/ijbs.63556
|View full text |Cite
|
Sign up to set email alerts
|

Enolase 1, a Moonlighting Protein, as a Potential Target for Cancer Treatment

Abstract: Enolase 1 (ENO1) is a moonlighting protein, function as a glycolysis enzyme, a plasminogen receptor and a DNA binding protein. ENO1 play an important role in the process of cancer development. The transcription, translation, post-translational modifying activities and the immunoregulatory role of ENO1 at the cancer development is receiving increasing attention. Some function model studies have shown that ENO1 is a potential target for cancer treatment. In this review, we provide a comprehensive overview of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 109 publications
2
41
0
1
Order By: Relevance
“…The other genes with higher RNA expression in Cluster 2 were ISG20 and CLIC3; both are implicated in tumor progression (Alsheikh et al, 2021; Hernandez‐Fernaud et al, 2017), suggesting they may contribute to the greater fold expansion we observed in the conditions containing 41BBL (Figure 2a). On the other hand, ENO1, which is a key glycolysis enzyme with pleiotropic roles in growth and differentiation (Qiao et al, 2021), was increased in RNA levels in clusters (3 and 5) that were mostly resulted from cells cultured with K562 alone or K562 expressing mIL15, suggesting a role in the phenotypic differences of the cytokine‐induced NK cells.…”
Section: Resultsmentioning
confidence: 99%
“…The other genes with higher RNA expression in Cluster 2 were ISG20 and CLIC3; both are implicated in tumor progression (Alsheikh et al, 2021; Hernandez‐Fernaud et al, 2017), suggesting they may contribute to the greater fold expansion we observed in the conditions containing 41BBL (Figure 2a). On the other hand, ENO1, which is a key glycolysis enzyme with pleiotropic roles in growth and differentiation (Qiao et al, 2021), was increased in RNA levels in clusters (3 and 5) that were mostly resulted from cells cultured with K562 alone or K562 expressing mIL15, suggesting a role in the phenotypic differences of the cytokine‐induced NK cells.…”
Section: Resultsmentioning
confidence: 99%
“…A more direct role of enolase and aldolase is suggested by studies that show these two enzymes have roles well beyond their well-known function in glycolysis. Enolase-1 has been shown to localize to the plasma membrane as a plasminogen receptor as well as function as a DNA binding protein in the process of transcription and has involvement in multiple signal transduction pathways [ 75 ]. Aldolase A has already been implicated as an actin-binding protein that regulates polymerization of actin [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…ENO1 is a multifunctional protein which implicated in critical biological progression pathways in cancers. As a glycolytic enzyme, ENO1 contributes to the Warburg effect and provides ATP to promote cancer development and progression [45]. In addition, ENO1 promotes the plasminogen activation system and upregulates integrin to enhance the migration and invasion of cancers [46][47][48]; ENO1 regulates gastric cancer cells stemness by stimulating glycolysis [49].…”
Section: Discussionmentioning
confidence: 99%